SINERGITAS PERAN KELUARGA DAN PEMERINTAH KOTA PEKALONGAN DALAM PENCEGAHAN TINDAK KEKERASAN PADA ANAK - Kusroh Lailiyah; Amelia Putri Nirmala (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah (Bappeda) Kota Pekalongan, 2023)
This study aims to find out the synergy between the role of the family and the Pekalongan City government in preventing acts of violence against children in Pekalongan City. This research is a library research. This study uses a qualitative approach through descriptive analysis methods based on literature studies obtained such as searches in books, journal articles and other digital materials from the internet which are then used as analysis material. The results of this study indicate that the family has a very important role in preventing acts of violence against children. Good and proper family education will be able to produce children who have good character as well. Children who have good and strong character will be able to protect themselves from various acts of violence. In addition, the government of Pekalongan City has also made many breakthroughs in efforts to prevent acts of violence against children. These efforts include forming a Community-Based Integrated Child Protection (PATBM) team at the village and sub-district levels, forming the PUSPAGA ELPePar Community-Based Family Education Center (PPKBM PUSPAGA ELPePar) in collaboration with the Indonesian Psychological Association (HIMPSI) Branch of the Ex-Residency of Pekalongan which provides free psychological counseling services for parents, as well as a child goes to school forum which provides free consultation services for children. In addition, the Pekalongan city government has also carried out socialization on violence against children involving community leaders and the media. With the synergy between the family and the government of Pekalongan City in carrying out their respective roles optimally, acts of violence against children in Pekalongan City can be suppressed and prevented. Keywords: Pekalongan City Government, child violence, Pekalongan LP-PAR, qualitative approach